PERANAN PENYIDIK POLRI DALAM PENANGANAN PERKARA TINDAK PIDANA KORUPSI DI KOTA SAMARINDA - Ridwan Lukman (Universitas 17 Agustus 1945 Samarinda, 2014)
Abstract Corruption is a violation of social rights and economic rights of the people. Corruption has become an extraordinary crime. Similarly, in the eradication measures can no longer be performed normally, but is charged with an extraordinary way. Corruption should not contain elements of direct financial harm countries or economies, for example suapmenyuap. Which is a despicable act is an abuse of power, discriminatory behavior by providing financial benefits, breach of trust, mental damage officials, dishonesty in competition and others Investigator Police as investigators in the handling of corruption. Then to complete the obligations of the national police investigators must cooperate with other relevant parties. Cooperation with other parties is referred to the legal relationship, because in doing the same work in a rule or law that are uncertain. Legal relationship with the other party can be an individual, legal entities and other government agencies.